2020
DOI: 10.3389/fphar.2020.562376
|View full text |Cite
|
Sign up to set email alerts
|

Quality Control of Radix Astragali (The Root of Astragalus membranaceus var. mongholicus) Along Its Value Chains

Abstract: Radix Astragali (RA), the root of Astragalus membranaceus var. mongholicus (Bunge) P.K. Hsiao, known as “Huangqi” in Chinese, has been used as a traditional herbal medicine or food in China for more than 2,000 years and is now consumed globally. Unfortunately, the increasing demand for RA has led to the overexploitation of its wild stock, as well as quality problems, including adulteration and contamination. Therefore, the sustainable cultivation of RA is urgently needed. In the present research, semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…In recent years, the effective ingredients of Chinese herbal medicine have attracted the attention of many scholars because of their multichannel and multitarget therapeutic effects. APS is one of the most commonly used in Chinese medicines for the treatment of diseases such as neuroinflammation and neurodegenerative diseases [26]. Preliminary studies in our laboratory have found that the water extract of Astragalus membranaceus and its active ingredient APS could effectively treat EAE mice, inhibit neuroinflammation and demyelination, and suppress the proliferation of MOG specific T cells [6].…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, the effective ingredients of Chinese herbal medicine have attracted the attention of many scholars because of their multichannel and multitarget therapeutic effects. APS is one of the most commonly used in Chinese medicines for the treatment of diseases such as neuroinflammation and neurodegenerative diseases [26]. Preliminary studies in our laboratory have found that the water extract of Astragalus membranaceus and its active ingredient APS could effectively treat EAE mice, inhibit neuroinflammation and demyelination, and suppress the proliferation of MOG specific T cells [6].…”
Section: Discussionmentioning
confidence: 95%
“…Bge. have been used as Traditional Chinese Medicines (TCMs) for more than 2,000 years [5]. Astragali Radix (AR) can tonify the middle-jiao and replenish qi, solidify the surface and promote diuresis, dispel sepsis and renew muscle [6].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the artificial inoculation technology for C. deserticola cultivation is becoming increasingly advanced, and the cultivated area is expanding on a yearly basis. Therefore, artificial cultivation of C. deserticola may be considered to resolve issues arising from a scarcity of medicinal and protected wild resources (Bi et al, 2020). Moreover, the development of a series of health products based on Cistanches Herba has resulted in a substantial expansion in the international influence of Cistanches Herba.…”
Section: Introductionmentioning
confidence: 99%
“…Besides production, VC research also focuses on other activities related to the supply chain, including distribution and marketing. VCs define the activities involved in different modes of production, while emphasizing the relationship between primary producers and other stakeholders in different production systems and their socio-economic impact (Bi et al, 2020). Although VC analyses have been widely used in various products, only a few studies have investigated the VCs of medicinal plants and their derivatives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation